Wait.

The second step where you moved just multiplied both sides doesn't make any sense. Shouldn't you make fraction. Doing it that way I got the answer 444447165.16

Is that right or is Archie right.

If you have

\(\displaystyle \frac{3}{5}-\frac{2}{5}=x\)

then you can just multiply both sides by 5 to get 3-2=5x

It's the same as combining the fractions to get \(\displaystyle \frac{3-2}{5}=x\)

You can either combine the fractions or just multiply both sides by the denominators.

\(\displaystyle x=\frac{1}{2}+\frac{1}{3}=\frac{3}{6}+\frac{2}{6}=\frac{5}{6}\)

\(\displaystyle 2x=1+\frac{2}{3}\)

\(\displaystyle 6x=3+2=5\)

is another way.

If x=5, then 2x=10 by multiplying both sides by 2, they are still equal and saying the same thing.

5=5, 5(2)=5(2), (3+2)=5, 2(3+2)=2(5)

If two sides are the same, then if you multiply all terms of both sides

by the same number, they will still be equal.

You should get used to adding fractions, so that it becomes easy,

however, multiplying by the denominators in this case is faster.